Update on the Management of Antibiotic Allergy - Thong, Bernard Yu-Hor (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2010)
Drug allergy to antibiotics may occur in the form of immediate or non-immediate (delayed) hypersensitivity reactions. Immediate reactions are usually IgE-mediated whereas non-immediate hypersensitivity reactions are usually non-IgE or T-cell mediated. The clinical manifestations of antibiotic allergy may be cutaneous, organ-specific (e.g., blood dyscracias, hepatitis, interstitial nephritis), systemic (e.g., anaphylaxis, drug induced hypersensitivity syndrome) or various combinations of these. Severe cutaneous adverse reactions manifesting as Stevens Johnson syndrome or toxic epidermal necrolysis (TEN) may be potentially life-threatening. The management of antibiotic allergy begins with the identification of the putative antibiotic from a detailed and accurate drug history, complemented by validated in-vivo and in-vitro allergological tests. This will facilitate avoidance of the putative antibiotic through patient education, use of drug alert cards, and electronic medical records with in-built drug allergy/adverse drug reaction prescription and dispensing checks. Knowledge of the evidence for specific antibiotic cross-reactivities is also important in patient education. Apart from withdrawal of the putative antibiotic, immunomodulatory agents like high-dose intravenous immunoglobulins may have a role in TEN. Drug desensitization where the benefits outweigh the risks, and where no alternative antibiotics can be used for various reasons, may be considered in certain situations. Allergological issues pertaining to electronic drug allergy alerts, computerized physician prescriptions and decision support systems, and antibiotic de-escalation in antimicrobial stewardship programmes are also discussed.